Some doubts about the impact of artificial intelligence on law. A tentative diagnosis to overcome it through new options and old friendships - Uscamayta, Gabriel Eduardo (2020)
This paper addresses some of the impacts that technologies will have on law in the not so distant future. In order to do so, I first address, by way of introduction, and in a didactic manner, one of the latest disruptive events of artificial intelligence in e-sports. I then use this short introduction to make some analogies in law. I then focus on the automation of legal tasks and raise the possibility of distinguishing between total automation and the automation of certain legal activities, with emphasis on the intelligent search of normative material as one of the most significant advances. Having said that, I go on to briefly analyze the situation of legal education in Peru and review whether there is any interest in technology. Finally, I argue about some alternatives to cushion the impact of artificial intelligence and new technologies in legal education. To this end, I propose the revaluation of some courses, but especially the bet on legal knowledge engineering, legal process analysis and legal management.